Genome-wide SNP data support species boundaries in sympatric Polylepis Ruiz & Pav. (Rosaceae) species from Bolivia and Ecuador - Jay Edneil C. Olivar; Marcus Lehnert; Walter Durka; Stefan Michalski; Christiane M. Ritz; Jana Ebersbach; Alexandra N. Muellner-Riehl; Claudia Segovia-Salcedo; Sofía Acosta-Villamarín; Katya Romoleroux; Erika Priscilla Muriel Mera; Emilio J. Trujillo; et al. (Molecular Phylogenetics and Evolution, 2026)

Hotspots of timber species declines in Nigeria: evidence from species distribution models under climate and land use change - Nina Münder; Tobias Fremout; Abubakar Bello; Wyclife Agumba Oluoch; Christine B. Schmitt; Alexandra N. Muellner-Riehl; João de Deus Vidal Junior (Regional Environmental Change, 2026)
Ongoing climate and land use changes pose significant threats to biodiversity and ecosystem services in Western Africa. High deforestation rates, combined with climate-driven range shifts, impact the distribution of tree species providing key ecosystem services such as timber. However, the distribution of timber species in Nigeria under climate and land use change is poorly understood. To address this knowledge gap, we assessed current and future (2041–2070) patterns of timber species richness and their implications for forest management by using individually tuned maximum entropy models for 108 native timber species under three climate change scenarios, accounting for current land use. Our models show up to 85 timber species concentrated in the southern moist forests, which are important biodiversity hotspots and centers of endemism in West Africa, while the northern savannas exhibit lower richness. Under all Shared Socio-Economic Pathways (SSPs), species richness changes range from slight increases to localized declines in southern regions. Up to 78% of timber species are predicted to lose suitable habitat under SSP1-2.6, with an average net loss of 36%, due to relatively little precipitation and increased temperature, while SSP3-7.0 and SSP5-8.5 show smaller losses due to higher increases in precipitation (27% and 23%). Generally, 42.3% of Nigeria was classified as unsuitable for timber species due to land use. Our findings highlight the importance of the southern moist forests of the Cross River and Ogun states as key refugia and connectivity corridors for native timber species. These results stress the need for targeted ecological restoration, connectivity improvement, and sustainable forest management, considering species vulnerability to climate change, to mitigate impacts on ecosystem services.

Sunda–Sahul floristic exchange and pathways into the Southwest Pacific: New insights from wet tropical forest trees - Laura Holzmeyer; Frank Hauenschild; Alexandra N. Muellner‐Riehl (Journal of Biogeography, 2023)
Aim Recent investigations on the floristic exchange between Southeast Asia and Australia have shown a clear dispersal directionality bias (West to East) of wet‐adapted plant taxa. However, dispersal routes and directions of wet forest taxa into the South Pacific remain insufficiently known. We here aimed to establish the most likely routes and directions of plant dispersal into the Southwest Pacific islands. Location Southeast Asia, East Asia, Australia, Southwest Pacific. Taxon Dysoxylum s.l. (Meliaceae). This includes Dysoxylum s.s., Didymocheton , Epicharis , Goniocheton , Pseudocarapa , and Prasoxylon . Method We sampled 75% of the species diversity in Dysoxylum s.l., covering the entire distribution range, all genera and major lineages. Phylogenetic relationships of 149 accessions were reconstructed using Bayesian Evolutionary Analysis and two internal constraints. The dispersal–extinction–cladogenesis variant, founder‐event speciation (DEC+J), was used for reconstructing the biogeographic history, and 100 Biogeographical Stochastic Mappings were simulated. Results Dysoxylum s.l. originated and firstly diversified in the western part of its current distribution range (including Indochina) during the Miocene to Pliocene, followed by an overall eastern range expansion towards Malesia, Australia and the Southwest Pacific in the Pliocene. Main Conclusions The south‐eastward expansion of lineages into Wallacea and Australia is in temporal agreement with the convergence of the Asian and Australian tectonic plates since the Miocene. Long‐distance dispersal is the main mechanism that led to the current distribution. Two dispersal pathways into the Southwest Pacific are identified, (1) through New Guinea and the Solomon Islands to Fiji, and (2) from New Zealand to Fiji. For both routes, Fiji was an important secondary source area for dispersal into the Southwest Pacific.

Biogeography of Neotropical Meliaceae: geological connections, fossil and molecular evidence revisited - Alexandra N. Muellner-Riehl; Blanca M. Rojas-Andrés (Brazilian Journal of Botany, 2022)
We here provide, first, a general introduction into the woody angiosperm family Meliaceae, including updated numbers of the genera and species found in different parts of the globe, paying attention to geographic centres of diversity and patterns of endemism. Second, and more specifically, we review the latest literature concerning land connections (i) between Eurasia and North America, (ii) between North America and South America, as well as (iii) dispersal paths between Africa and South America that have existed since the proposed evolutionary origin of modern Meliaceae, i.e. from the Upper Cretaceous onwards (ca. 100 Million years ago). Comparing geological evidence with the fossil record as well as biogeographic studies, there is indication that the nowadays pantropically distributed family has made use of all these three routes. Five out of the eight modern Neotropical genera have a fossil record, namely Carapa Aubl., Cedrela P. Browne, Guarea F. Allam., Swietenia Jacq., and Trichilia P. Browne. Carapa and Trichilia have a modern transatlantic disjunction (distribution in Africa, Central and South America), and a fossil record in Africa and North/Central America ( Trichilia ), or Africa and Eurasia ( Carapoxylon ). Cedrela has a rich fossil record in Eurasia and the Americas. The global decrease in temperatures and a lack of Cedrela fossils in North America from the Late Miocene onwards suggest the genus had gone extinct there by that time, leading to its modern distribution in Central and South America. Oligocene to Pliocene fossils of Guarea , Swietenia and Trichilia in Central American key regions support biotic interchange between North and South America at various times.

Invertebrate‐mediated dispersal plays an important role in shaping the current distribution of a herbaceous monocot - Yong‐Sheng Chen; Chun‐Xia Zeng; Alexandra N. Muellner‐Riehl; Zhi‐Heng Wang; Lu Sun; Johann Schinnerl; Sumet Kongkiatpaiboon; Yuichi Kadota; Xiang‐Hai Cai; Gao Chen (Journal of Biogeography, 2021)
Aim Invertebrate‐mediated dispersal has previously been proposed to promote angiosperm diversification and distribution. However, little is known about the specific impact of invertebrate‐mediated dispersal on the biogeography and current distribution of plants. We aim to infer the influence of vespicochorous (hornet) and myrmecochorous (ant) dispersal on the historical biogeography of herbaceous monocot species. Location Southeast Asia, East Asia, Australia, North America. Taxon Family Stemonaceae. Method We sampled ca. 75% of the species diversity in Stemonaceae (28 out of 37 species), covering the entire distribution range of the family, to reconstruct the biogeographic history of this family. Using phylogenetic logistic regression analyses, we then tested the relationship between dispersal modes and geographic distributions. Results Stemonaceae originated on the Asian mainland during the late Cretaceous and then dispersed to North America, the western Malay Archipelago and eastern Malay Archipelago and Australia between the late Cretaceous and Pliocene. Geographical ranges of ant‐ versus hornet‐dispersed Stemonaceae species are significantly different, with vespicochorous species having broader distribution ranges than myrmecochorous species. Main conclusions Invertebrate‐mediated dispersal in Stemonaceae may promote narrow endemism and play an important role in shaping the current distribution of species. Most lineages dispersed by ants failed to cross biogeographic barriers and exhibit limited range expansion overland. Vespicochorous lineages were able to cross oceanic barriers and occupy larger continental areas and/or occur on oceanic islands.

Origins of global mountain plant biodiversity: Testing the ‘mountain‐geobiodiversity hypothesis’ - Alexandra N. Muellner‐Riehl; Jan Schnitzler; W. Daniel Kissling; Volker Mosbrugger; Kenneth F. Rijsdijk; Arie C. Seijmonsbergen; Hannes Versteegh; Adrien Favre (Journal of Biogeography, 2019)
Aim Our objective is to analyse global‐scale patterns of mountain biodiversity and the driving forces leading to the observed patterns. More specifically, we test the ‘mountain geobiodiversity hypothesis’ (MGH) which is based on the assumption that it is not mountain‐uplift alone which drives the evolution of mountain biodiversity, but rather the combination of geodiversity evolution and Neogene and Pleistocene climate changes. We address the following questions: (a) Do areas of high geodiversity and high biodiversity in mountains overlap, that is can mountain geodiversity predict mountain biodiversity? (b) What is the role of Pleistocene climate change in shaping mountain biodiversity? (c) Did diversification rate shifts occur predominantly with the onset of more pronounced climate fluctuations in the late Neogene and Pleistocene fostering a ‘species pump’ effect, as predicted by the MGH? Location Global. Taxon Vascular plants. Methods We used generalized linear models to test to what extent vascular plant species diversity in mountains is explained by net primary productivity (NPP), geodiversity and Pleistocene climate fluctuations (i.e. changes in temperature between the Last Glacial Maximum [LGM] and today). In addition, we compiled dates of diversification rate shifts from mountain systems and investigated whether these shifts occurred predominantly before or after the global major climatic fluctuations of the late Neogene and Pleistocene. Results Both NPP and elevation range show a positive relationship, whereas Pleistocene climatic fluctuations show a negative impact on plant species diversity. The availability of climatic niche space during the LGM differs markedly among mountain systems. Shifts to higher diversification rates or starts of radiations showed the highest concentration from the late Miocene towards the Pleistocene, supporting the MGH. The most commonly inferred drivers of diversification were key innovations, geological processes (uplift) and climate. Main conclusions Our analyses point towards an important role of historical factors on mountain plant species richness. Mountain systems characterized by small elevational ranges and strong modifications of temperature profiles appear to harbour fewer radiations, and fewer species. In contrast, mountain systems with the largest elevational ranges and stronger overlap between today´s and LGM temperature profiles are also those where most plant radiations and highest species numbers were identified.

The influence of the Gondwanan breakup on the biogeographic history of the ziziphoids (Rhamnaceae) - Frank Hauenschild; Adrien Favre; Ingo Michalak; Alexandra N. Muellner‐Riehl (Journal of Biogeography, 2018)
Aim We investigated whether the fossil‐rich and cosmopolitan buckthorn family (Rhamnaceae, dating back to the Cretaceous) was influenced by vicariance events following the Gondwanan breakup. To answer this question, we focused on the ziziphoid lineage of the buckthorn family, because extant ziziphoid taxa comprise tribes and genera exclusively or at least predominantly distributed in the Southern Hemisphere (Australia, Africa, and South America). Location World‐wide. Methods We generated a DNA alignment of 26,989 bp (from plastid, mitochondrial, and nuclear genomes), comprising 575 taxa of Rhamnaceae and related families, including all major lineages within Rhamnaceae and closely related families. We used nine internal fossils to set constraints in our molecular dating analyses. We used ‘BioGeoBEARS’ in R to reconstruct ancestral areas in order to infer the impact of vicariance events on the ziziphoids caused by Gondwanan fragmentation. Results Our biogeographic analyses illustrate that the ziziphoid lineage was influenced by both long‐distance dispersal and Gondwanan breakup vicariance events. Yet, these vicariance events cannot explain all divergence events at the backbone of this lineage. Main conclusions Our study highlights that a taxon's distribution throughout the Northern Hemisphere can be the result of vicariance, but this process may be obliterated by more recent long‐distance dispersal (LDD). Our study also highlights that sufficiently old taxa may sometimes constitute better models to investigate the impact of Gondwanan‐driven vicariance than taxa with a current disjunct distribution in the Southern Hemisphere.

Out‐of‐Tibet: the spatio‐temporal evolution of Gentiana (Gentianaceae) - Adrien Favre; Ingo Michalak; Chih‐Hsiung Chen; Jenn‐Che Wang; James S. Pringle; Sabine Matuszak; Hang Sun; Yong‐Ming Yuan; Lena Struwe; Alexandra N. Muellner‐Riehl (Journal of Biogeography, 2016)
Aim We investigated the historical biogeography and diversification of Gentiana L. (Gentianaceae). Our study depicts the origin and dispersal routes of this alpine genus, and the role of the uplift of the Qinghai–Tibet Plateau ( QTP ) and past climate changes as triggers for its diversification. Location Tibeto‐Himalayan region and world‐wide mountain habitats. Methods Our sampling represents more than 50% of the extant Gentiana species, including all sections across their entire geographical ranges. We investigated the evolutionary history of Gentiana using phylogenetic reconstructions (maximum likelihood and Bayesian inference) of ITS , atp B– rbc L and trn L– trn F sequences, as well as molecular dating with beast . We tested two approaches of ancestral area reconstructions ( DEC , DIVA ) in BioGeo BEARS and investigated diversification rates using BAMM . Results The common ancestor of Gentiana and subtribe Gentianinae lived in the QTP region at around 34 (25–45) million years ago (Ma), and 40 (29–52) Ma respectively. From the surroundings of the QTP , Gentiana lineages dispersed to eastern China, Taiwan, Europe, North and South America, Australia and New Guinea, from mid‐Miocene onward ( c . 15 Ma–present), with only one older dispersal event to Europe ( c . 37–21 Ma). Diversification rates gradually increased over time, and two switches of diversification rates were identified in Gentianinae ( c . 7 Ma, simultaneously in the Pneumonanthe / Cruciata lineage and in Tripterospermum ). Main conclusions Gentiana existed in the QTP region throughout most of its uplift history following the India‐Asia collision. This region acted as the primary source area for dispersals to many areas of the world. Because steady increase in diversification rates coincides with the extension of the QTP , we argue that the museum theory rather than the explosive radiation theory prevails for gentians in this region, although rare shifts of diversification rates are associated with niche shifts across the alpine/subalpine ecotone.

Dispersal routes between biodiversity hotspots in Asia: the case of the mountain genus Tripterospermum (Gentianinae, Gentianaceae) and its close relatives - Sabine Matuszak; Alexandra N. Muellner‐Riehl; Hang Sun; Adrien Favre (Journal of Biogeography, 2016)
Aim We investigated the biogeography of the subtropical mountain genus Tripterospermum Blume (Gentianaceae), disjunctly distributed at the southern fringe of the Qinghai–Tibetan Plateau ( QTP ) and other mountain systems within the biodiversity hotspots of Southeast Asia. This study reveals dispersal routes among these areas. Location East China, Indochina, Japan, the Philippines, southeastern fringe of the Qinghai–Tibetan Plateau (southern Himalaya and Hengduanshan), Taiwan, Wallacea. Methods The evolutionary history of Tripterospermum was studied using the phylogenetic reconstructions (Maximum Likelihood and Bayesian Inference using ITS , atpB–rbcL and trnL–trnF ), molecular dating (using BEAST with a relaxed clock model and fossil constraints), and two approaches of ancestral area reconstructions ( DEC , S‐ DIVA ). Our sampling design included 82% of the extant species of subtropical Gentianinae ( Tripterospermum , Metagentiana , Sinogentiana and Crawfurdia ) as ingroup, and Kuepferia , Gentiana and other Gentianaceae genera as outgroups. Results Subtropical Gentianinae originated at the southeastern fringe of the QTP (the southern Himalaya and Hengduanshan) between 16 and 35 million years ago (Ma). With a crown age estimated to be 2.7–8.8 million years (Myr), Tripterospermum originated at the southeastern fringe of the QTP , from where it dispersed to East China, Indochina, Sundaland, Taiwan, Japan and Wallacea. Main conclusions For Tripterospermum , the southern Himalaya and the Hengduanshan have acted as a source area for the colonization of East and Southeast Asia. This study depicts dispersal routes among the biodiversity hotspots neighbouring the QTP and those located on Sundaland and Wallacea. Mountain plants seem to have colonized Wallacea using a northern route via Taiwan rather than a more southern route via Sundaland. The latter route has previously been recorded for many lowland lineages. Because Tripterospermum species‐producing berries have dispersed more often across geographical barriers than those producing capsules, we hypothesize that avian transportation of berry‐like fruits might have facilitated their dispersal.